Neuroplastic Effects in Patients With Traumatic Brain Injury After Music-Supported Therapy - Vik, Berit Marie Dykesteen; Skeie, Geir Olve; Specht, Karsten (Frontiers in Human Neuroscience, 2019)
Abstract The orbitofrontal cortex is known for being involved in distinctive cognitive and behavioural operations. Damage to the orbitofrontal and ventromedial prefrontal cortices often occurs following traumatic brain injury and can lead to disorders of personality, affect, motivation, impulsive behaviour, and social cognition. Here we focus on cognitive systems specifically for social behaviour following mild to moderate traumatic brain injury. We performed a music-supported intervention on patients with impairment in social interaction and cognitive deficits following mild to moderate traumatic brain injury. The patients were in a stable phase of acquired brain injury two years post injury. Additional two control groups of healthy participants were included in the study. We assessed the participants with neuropsychological tests, fMRI pre-post intervention, and semi-structured interviews to obtain subjective behavioural data. We present significant evidence for a qualitative increase of social interaction in the patient group and normalization of activation in orbitofrontal cortex after intervention. We propose a causal relationship between the training of piano playing and neuroplastic changes in orbitofrontal cortex followed by improved social functioning and enhanced cognitive performance.